Characterization of the gut microbiota in people with different levels of obesity - Li, Ergan; Wang, Senlin; Li, Youqin; Liuli, Anke; Liang, Meifang; Huang, Jian; Li, Yan; Li, Haifang; Feng, Zhonghui (Frontiers in Microbiology, 2025)
PurposeWith the evolution of dietary habits, obesity has emerged as a significant global health issue. Numerous studies have demonstrated a close association between obesity and gut microbiota; however, the specific contribution of gut microbiota to varying degrees of obesity remains inadequately understood. Consequently, this study aims to characterize the gut microbiota of individuals across different obesity severity levels.MethodsWe conducted a comprehensive characterization of the gut microbiome in Chinese obese patients and a healthy control group through the application of 16S rRNA gene sequencing, supplemented by metagenomic sequencing. The study cohort was stratified into five distinct categories based on body mass index (BMI): healthy, overweight, and obesity grades I, II, and III.ResultsIn obese populations, the gut microbiome structure shifted significantly, with beneficial genera like Faecalibacterium, Roseburia, and Ruminococcus decreasing, and potentially harmful genera such as Blautia, Collinsella, and Streptococcus increasing. These changes impacted host metabolic pathways, including ribosome synthesis, RNA polymerase activity, and DNA repair. Clinical analyses also revealed strong links between specific genera and metabolic markers like lipid metabolism and insulin resistance.ConclusionPopulations with different obesity traits show unique changes in gut flora. The level of dysbiosis, or imbalance in intestinal microbiota, rises with obesity. These microbial changes are linked to host metabolism, indicating that targeting harmful bacteria and supplementing with beneficial ones from normal-weight populations could effectively reduce obesity.